Estonian Tax Structure - Trasberg, Viktor (Estonian Discussions on Economic Policy, 2014)
The paper analyses Estonian tax structure changes during the last decade and critically assesses the current situation.The country’s tax mix is rather unique among EU countries – it has one of the highest proportions of consumption taxes in total taxes and the lowest level of capital and profit taxes. Such an unbalanced tax structure creates risks for public finances, limits revenue collection and distorts the business environment.